Carbon, Capital, and Concepts: A Review of New Social Science Vocabularies in the Globalisation–Climate Change Debate - Belay Sitotaw Goshu (Britain International for Academic Research (BIAR) Publisher, 2026)
Climate change represents a fundamental challenge to the conceptual apparatus of the social sciences. The phenomena of global warming carbon flows that ignore borders, supply chains that span continents and vulnerabilities that are unequally distributed – cannot be adequately captured by traditional vocabularies centered on the nation‑state, international cooperation, or technical mitigation. This review article synthesises the new conceptual vocabulary that has emerged in social science scholarship since the early 2000s, focusing on concepts that explicitly reframe climate change as a problem of globalisation, power, and justice. I identify five thematic clusters: (1) spatial re‑imaginings (planetary boundaries, anthroposphere, transnational governance); (2) power and historical inequality (carbon democracy, climate colonialism, ecological unequal exchange); (3) justice beyond distribution (loss and damage, just transition, slow violence); (4) critiques of market‑based solutions (carbon offsets, green growth/degrowth); and (5) temporal and geo‑social frames (Anthropocene vs. Capitalocene). The review argues that these concepts collectively perform three critical functions: they expose the spatial asymmetries embedded in globalisation, challenge methodological nationalism, and open normative debates about climate justice and transformation. The article concludes by identifying gaps notably the under‑theorisation of climate‑finance instruments and the marginalisation of non‑Western conceptual traditions and proposes a research agenda for the next generation of critical climate social science.